Effects of processing sorghum grain on dairy calf performance - I.E.O. Abdelgadir; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1994)
Two trials evaluated the effect of processing sorghum grain on performance of young dairy calves. In trial 1, newborn Holstein calves (49 heifers and 27 bulls) were blocked by age and sex and assigned randomly to each of three calf starters containing either raw, roasted (Jet-Pro®) at 280 degrees F, or conglomerated (Jet-Pro®) sorghum grain. The conglomeration process consisted of grinding the grain, adding water, and pelleting the mixture, then roasting it. Raw and roasted sorghum grains were ground through a .125-inch screen and included in complete pellet starters, whereas conglomerated sorghum grain pellets were mixed with the other ingredients of the starter, which were pelleted. Starters were offered ad libitum from birth to 8 wk of age. The raw sorghum grain starter was palatable and supported acceptable growth rates, but processing did not further enhance calf performance. In trial 2, roasted and conglomerated sorghum grains were ground through a .125- inch screen and included in pelleted starters fed ad libitum to Holstein calves (21 heifers and 28 bulls) from birth to 8 wk of age. Feed consumption and body weight gain were not affected by method of grain processing. However, 22% of calves on the conglomerated sorghum grain starter bloated sometime during the post-weaning period, which may have resulted in reducing feed intake. Measures to ensure maintenance of the rumen environment may be necessary, if a potential benefit of conglomerating sorghum grain for young dairy calves is to be realized.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Sorghum grain; Processing; Calf starters